Cultural heritage interpretation in museum - its relation to visitors’ experience and satisfaction / Hamimi Omar and Norhanim Abdul Razak - Omar, Hamimi; Abdul Razak, Norhanim (2015)
Apart from being the place to preserve unique and diverse cultural heritage resources, museum also function as an attraction to visitors. In parallel with the development of museums as tourist attraction, public funded museums have been encouraged to focus on the needs of their visitors. They need to be places that people want to go to, see and experience the important aspects of the community within the destination. Museum presentations should be able to connect the visitors with the heritage values of the community. In this sense, the process of communicating or explaining to visitors the significance of the place or resources they are visiting is important. Such process is known as heritage interpretation. An effective interpretation should be able to reveals meanings behind historic places, their people and their stories. In this paper, the role of interpretation process on the experience and satisfaction of visitors to museum is explored. Location of the study is at Paddy Museum (Muzium Padi) in Alor Setar Kedah. Findings revealed that positive associations between effective interpretation and visitors’ satisfaction are important. Academic and managerial implications are discussed.